Impact of geriatric syndromes on anticoagulation prescription in older adults with atrial fibrillation. (4th March 2022) - Tan, Li Feng; Soh, Rodney; Koo, Christopher; Goh, Wilson; Shen, Goy; Lim, Jiayi; Seetharaman, Santhosh; Merchant, Reshma A.
Abstract: Background: Atrial fibrillation (AF) is common in older adults. CHA2DS2-VASC (congestive heart failure, hypertension, age ≥75 (doubled), diabetes mellitus, prior stroke or transient ischemic attack (doubled), vascular disease, age 65–74, female) and HASBLED(Hypertension, Abnormal Renal/Liver Function, Stroke, Bleeding History or Predisposition, Labile INR, Elderly, Drugs/Alcohol Concomitantly) are the most established risk stratification tools in assessing suitability for anticoagulation in AF. However, there are no established screening tools for geriatric syndromes on anticoagulation risks in older adults. Objective: This study examined the association of anticoagulation prescription with geriatric syndromes. Methods: Older adults 65 years and above admitted to a tertiary hospital with atrial fibrillation and CHA2DS2-VASC score ≥ 2. Data on demographics, function (modified Barthel's Index (MBI)), cognition (mini-cog), frailty (Edmonton Frail Scale (EFS) and FRAIL), geriatric syndromes (EFS), sarcopenia (SARC-F), HASBLED and CHA2DS2-VASC were collected. Results: 150 patients aged 65 and above (mean age 79.4 ± 7.1 years) with AF were recruited. 101 (67%) participants were anticoagulated, in univariate analysis comparing those who were anticoagulated with those who were not, age (OR 0.94; 95% CI 0.89−0.99), chronic kidney disease (OR 0.39; 95% CI 0.19−0.80), frailty (OR 0.77; 95% CI 0.60−0.98) and functional status by Barthel's Index (OR 0.75; 95% CI 0.57−0.97) were significantly associated with anticoagulation prescription. In multivariate analysis, age (OR 0.93; 95% CI 0.88−0.99) and CKD (OR 0.35; 95% CI 0.16−0.76) remained significant. There was no significant difference in CHA2DS2-VASC, HASBLED, MBI or falls between the groups. Conclusions: Age and CKD were significantly associated with anticoagulation prescription in patients with AF. Further studies on the impact of geriatric syndromes on anticoagulation prescription and outcomes in older adults are needed with specific guidelines for patients with geriatric syndromes and AF.